Surface-treated steel sheet
By forming a chemical conversion coating on the surface of the zinc plating layer or zinc alloy coating in a short time, and forming a plurality of concentrated parts near the interface between the coating and the coating, the problem of insufficient corrosion resistance and conductivity in the prior art is solved, and a surface-treated steel plate with excellent corrosion resistance and conductivity is realized.
Patent Information
- Application Number
- CN202380063819.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-06
- Filing Date
- 2023-10-06
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has shortcomings in improving the corrosion resistance of chromate-free treatment, especially when the coating does not contain Mg and Al, it is difficult to achieve the formation of the chemical conversion coating, resulting in insufficient corrosion resistance and electrical conductivity.
By forming a chemical conversion film on the surface of the zinc plating layer or zinc alloy plating layer in a short time, and forming a plurality of specific elements concentrated areas near the interface between the plating layer and the film, the barrier property and inhibitor effect of the film are improved.
The corrosion resistance and conductivity of the surface-treated steel plate are significantly improved, and the corrosion resistance and white rust can be effectively prevented in high-demand environments.
Smart Images

Figure CN119855942A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface treated steel plate.
[0002] This application claims priority based on Tokugan Application No. 2022-161691 filed in Japan on October 6, 2022 and Tokugan Application No. 2022-161692 filed in Japan on October 6, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] Conventionally, plated steel sheets (zinc-based plated steel sheets) having a plated layer mainly composed of zinc formed on the surface of a steel sheet have been used in a wide range of applications such as automobiles, building materials, and home electrical appliances.
[0004] In addition, the following methods are generally known and put into practical use: a method of subjecting the surface of such a zinc-plated steel sheet to a chromate treatment using a treatment solution containing chromic acid, dichromic acid or a salt thereof as a main component for the purpose of imparting corrosion resistance, paint adhesion, etc.; a method of subjecting the surface of the zinc-plated steel sheet to a treatment using a metal surface treatment agent that does not contain chromium; a method of subjecting the surface of the zinc-plated steel sheet to a phosphate treatment; a method of subjecting the surface of the zinc-plated steel sheet to a treatment using a silane coupling agent monomer; a method of subjecting the surface of the zinc-plated steel sheet to an organic resin coating treatment, etc.
[0005] In recent years, in particular, various regulations have been implemented to control hexavalent chromium compounds that may have adverse effects on the environment and human body, and the development of metal surface treatment agents that do not contain chromium has been promoted. As metal surface treatment agents that do not contain chromium, there is a technology that uses oxides or hydroxides of Group 4 metals such as Ti and Zr.
[0006] For example, Patent Document 1 discloses a chromate-free chemical conversion treated steel sheet, in which a galvanized steel sheet or a zinc alloy-plated steel sheet is used as a substrate, and a chemical conversion treatment film in which an oxide or hydroxide of a valve metal and a fluoride coexist and the oxide exhibits high insulation resistance is formed on the surface of the substrate.
[0007] In addition, Patent Document 2 discloses a hot-dip galvanized alloy steel sheet with excellent corrosion resistance, wherein a chemical conversion film having one or more of a hydroxide, oxide, oxyacid, oxyacid, and fluoride of a valve metal as a main component is formed on a zinc alloy plating layer containing Mg via an interface reaction layer containing one or more of magnesium fluoride, magnesium phosphate, and a composite compound of magnesium and a valve metal oxyacid. In Patent Document 2, a high white rust resistance (corrosion resistance) is exhibited by forming an interface reaction layer containing Mg by using a zinc alloy plating layer containing Mg as a base.
[0008] In addition, Patent Document 3 discloses a hot-dip galvanized alloy steel sheet having excellent corrosion resistance, wherein a composite chemical conversion film of Ti and V is formed on a Zn-Al alloy plating layer via an Al-F interface reaction layer. In Patent Document 3, a high white rust resistance is exhibited by forming an Al-F reaction layer using a zinc alloy plating layer containing Al as a base.
[0009] In addition, Patent Document 4 discloses a chromate-free precoated metal sheet, characterized in that it is a chromate-free precoated metal sheet having an upper coating film (α) formed on at least one side of the metal sheet, wherein a base treatment layer (β) is provided between the metal sheet and the upper coating film (α) by applying a base treatment agent and drying the base treatment agent, wherein the base treatment agent is prepared by combining (1) a film-forming component (X) and (2) an inhibitor component (Y), wherein the (1) film-forming component (X) contains an organic silicon compound (C) and at least one cationic organic resin (D) selected from a polyurethane resin, a phenolic resin, and an epoxy resin, wherein the organosilicon compound (C) is obtained by reacting a silane coupling agent (A) containing an amino group in the molecule with a silane coupling agent (B) containing a glycidyl group in the molecule, and has a cyclic siloxane bond and a chain siloxane bond in the structure, and the existence ratio of the cyclic siloxane bond to the chain siloxane bond is measured by 1090 to 1100 cm-1 of the cyclic siloxane bond by FT-IR reflection method -1 The absorbance (C1) is similar to that of 1030-1040 cm-1, which indicates the chain siloxane bond. -1 The absorbance ratio (C2) [C1 / C2] is expressed as 0.4 to 2.5; the (2) inhibitor component (Y) is an inhibitor component (Y) comprising at least one metal compound (E) selected from titanium compounds and zirconium compounds, a phosphoric acid compound (J) and a fluorine compound (F), wherein when the above-mentioned metal compound (E) is a fluorometal complex (E'), the above-mentioned fluorine compound (F) may not be present.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2002-194558
[0013] Patent Document 2: Japanese Patent Application Publication No. 2007-23309
[0014] Patent Document 3: Japanese Patent Application Publication No. 2003-306777
[0015] Patent Document 4: Japanese Patent Application Publication No. 2012-237065 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The technologies disclosed in Patent Documents 1 to 3 are excellent technologies that have been put into practical use as surface-treated steel sheets subjected to chromate-free surface treatment with excellent corrosion resistance. In order to improve the corrosion resistance of chromate-free treatment, as described in Patent Documents 2 and 3, a technology of forming a reaction layer containing metal elements contained in the plating layer is used. However, it is known that these prior arts have insufficient corrosion resistance due to the increase in customer demand in recent years.
[0018] For example, in the case of galvanized steel sheets using a coating layer containing no Mg or Al, it is difficult to form the above-mentioned reaction layer as described in Patent Documents 2 or 3, and there is a problem of insufficient corrosion resistance in the flat portion (plane portion) and the processed portion. In addition, even in the case of galvanized steel sheets using a coating layer containing Mg or Al in the coating layer, when a chemical conversion coating (skin film) is formed in a continuous hot-dip steel sheet manufacturing line, from the perspective of productivity, the time from applying the chemical conversion treatment liquid to the surface of the zinc-based plated steel sheet to the formation of the chemical conversion treatment coating by drying is very short, within 5 seconds, so the Mg and Al contained in the Zn phase of the zinc alloy coating layer are very small, so it is not easy to form the above-mentioned reaction layer on the Zn phase of the coating layer, and there is a problem of insufficient corrosion resistance.
[0019] Furthermore, in Patent Document 4, an organic resin must be contained as a film-forming component. Therefore, even if the coating film is excellent in corrosion resistance and coating film adhesion, there is a problem that the conductivity is poor.
[0020] Under such circumstances, a surface-treated steel sheet having excellent corrosion resistance (white rust resistance) and electrical conductivity is required in both a processed portion and a flat portion.
[0021] The present invention aims to provide a surface treated steel sheet having excellent corrosion resistance and electrical conductivity, based on a surface treated steel sheet in which a zinc-plated steel material having a plating layer containing zinc or a zinc alloy on the surface of the steel material has a chromate-free chemical conversion coating on the surface.
[0022] Means for solving problems
[0023] The higher the barrier property (the property of not allowing corrosion factors such as water or chloride ions to pass through) of the chemical conversion coating, the higher the corrosion resistance of the surface treated steel material with the chemical conversion coating. In addition, in the part where the chemical conversion coating is damaged due to cracking, etc., the higher the effect (inhibitor effect) of preventing corrosion of the plating layer by the dissolution of substances (mainly metal elements) in the chemical conversion coating when water adheres, the higher the corrosion resistance such as white rust resistance.
[0024] As described above, the chemical conversion coatings disclosed in Patent Documents 1 to 3 have both barrier properties and inhibitor effects, but in an environment requiring higher white rust resistance than before, each property is not sufficient, and there is a risk that the plating layer may corrode and white rust may form at an early stage.
[0025] In view of such circumstances, the present inventors have studied methods for improving the barrier properties and inhibitor effect of a chemical conversion coating from the viewpoint of conductivity, based on the premise that the chemical conversion coating does not contain an organic resin.
[0026] As a result, it was found that when a chemical conversion coating is formed on the surface of a zinc-plated layer or a zinc alloy-plated layer in a short period of time, in addition to controlling the concentration of each element, a plurality of specific element-concentrated sites are formed between the vicinity of the interface between the Zn phase of the zinc-plated layer or the zinc alloy-plated layer and the chemical conversion coating and the surface of the chemical conversion coating, thereby improving the barrier properties of the chemical conversion coating and dramatically improving the corrosion resistance.
[0027] The present invention has been made based on the above findings. The gist of the present invention is as follows.
[0028] [1] A surface-treated steel sheet according to one embodiment of the present invention comprises:
[0029] Base steel plate,
[0030] The plating layer formed on the surface of the base steel plate, and
[0031] A film formed on the surface of the above-mentioned plating layer,
[0032] The Zn concentration of the above-mentioned plating layer is 40 mass % or more and 100 mass % or less, and the Mg concentration is 0 mass % or more and less than 4.0 mass %,
[0033] When the concentrations of C, O, F, Mg, Al, Si, P, Ti, V, Zn, and Zr are continuously measured by line analysis along the thickness direction from the coating layer toward the surface of the surface-treated steel sheet,
[0034] The position where the Zn concentration first reaches 35.0 mass % or less is set to be the interface between the above-mentioned plating layer and the above-mentioned film,
[0035] The boundary region is defined as a region including the interface and between a range of 10 nm from the interface on the plated layer side and a range of 15 nm from the interface on the film side in the thickness direction.
[0036] The range of 10 nm from the center of the interface and the surface of the film in the thickness direction on the surface side is defined as the center of the film.
[0037] In this case, the surface-treated steel sheet satisfies at least one of the following formulas (1) to (3) and satisfies (4) to (12).
[0038] Dti≥5.0 (1)
[0039] Dzr≥5.0 (2)
[0040] Dv≥5.0 (3)
[0041] Dti+Dzr+Dv≤25.0 (4)
[0042] Bc<10.0 (5)
[0043] 5.0 / M≤Amg≤25.0 (6)
[0044] 0.5≤Bmg≤5.0 (7)
[0045] 15.0 / M≤Af≤40.0 (8)
[0046] 0.5≤Bf≤15.0 (9)
[0047] Amg / Bmg≥2.0 (10)
[0048] Af / Bf≥2.0 (11)
[0049] Bsi<5.0 (12)
[0050] wherein Dti is the maximum concentration of Ti in mass % between the interface and the center of the thickness direction from the interface to the surface,
[0051] The Dzr is the maximum concentration of Zr in mass % between the interface and the center of the thickness direction from the interface to the surface,
[0052] The Dv is the maximum concentration of V in mass % between the interface and the center of the thickness direction from the interface to the surface,
[0053] The above-mentioned Bc is the average concentration of C in the above-mentioned central part of the above-mentioned film in terms of mass %,
[0054] Amg is the maximum concentration of Mg in the boundary region of the film in terms of mass %,
[0055] The above-mentioned Bmg is an average concentration of Mg in the above-mentioned central part of the above-mentioned film in terms of mass %,
[0056] Af is the maximum concentration of F in the boundary region of the film in terms of mass %,
[0057] The above-mentioned Bf is the average concentration of F in the above-mentioned central part of the above-mentioned film in terms of mass %,
[0058] The above-mentioned Bsi is the average concentration of Si in the above-mentioned central part of the above-mentioned film in terms of mass %,
[0059] When the Mg concentration of the plating layer is 0 mass % or more and less than 1.0 mass %, the M is a constant of 1. When the Mg concentration of the plating layer is 1.0 mass % or more and less than
[0060] In the case of 4.0 mass %, the above-mentioned M is a constant of 2.
[0061] [2] The surface-treated steel sheet according to [1] may further satisfy the following formula (13).
[0062] 0≤Cmg<5.0(13)
[0063] Here, the Cmg is the concentration of Mg expressed in mass % at a position 10 nm from the interface on the plating layer side in the thickness direction of the plating layer.
[0064] [3] The surface-treated steel sheet according to [1] or [2] may further satisfy the following formulas (14) to (16).
[0065] 5.0≤Aal≤20.0 (14)
[0066] 0.2≤Bal≤5.0 (15)
[0067] Aal / Bal≥5.0 (16)
[0068] Here, the Aal is the maximum concentration of Al in the boundary region expressed in mass %, and the Bal is the average concentration of Al in the central portion of the film expressed in mass %.
[0069] [4] The surface-treated steel sheet according to any one of [1] to [3] may further satisfy the following formulas (17) to (18).
[0070] 10.0≤Ap≤25.0 (17)
[0071] 0.5≤Bp≤8.0 (18)
[0072] Here, the Ap is the maximum concentration of P in the boundary region expressed in mass %, and the Bp is the average concentration of P in the central portion of the film expressed in mass %.
[0073] [5] The surface-treated steel sheet according to any one of [1] to [4] may further satisfy the following formula (19).
[0074] 1.0≤Bzn≤30.0 (19)
[0075] Here, the Bzn is an average concentration of Zn in the central portion of the film in mass %.
[0076] [6] The surface-treated steel sheet according to any one of [1] to [5] may further satisfy the following formula (20).
[0077] Af / Bf≥2.5 (20)
[0078] Effects of the Invention
[0079] According to the above aspects of the present invention, it is possible to provide a surface-treated steel sheet having excellent corrosion resistance and electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 It is a schematic diagram showing an example of a cross section of a surface-treated steel sheet according to the present embodiment.
[0081] Figure 2 This is a diagram showing an example of elemental analysis results in the thickness direction obtained using a FE-TEM equipped with an energy dispersive X-ray analyzer. DETAILED DESCRIPTION
[0082] A surface treated steel plate according to an embodiment of the present invention (surface treated steel plate according to the present embodiment) is described. For the numerical ranges limited by "to" described below, the values at both ends are included in the range as the lower limit and the upper limit. On the other hand, for the numerical values expressed as "exceeding" or "below", the value is not included in the numerical range. In addition, the units of ratios (for example, the ratio of Amg to Bmg described later, i.e. Amg / Bmg) are all dimensionless.
[0083] like Figure 1 As shown in , the surface treated steel sheet 1 of the present embodiment has a base steel sheet 10, a plating layer 20 formed on the surface of the base steel sheet 10, and a film 30 formed on the surface of the plating layer 20. The plating layer 20 is a zinc plating layer or a zinc alloy plating layer containing 0% or more and less than 4.0% of Mg. From the perspective of conductivity, it is not preferred to further have a film containing an organic resin on the film 30. Therefore, it may also be composed of a base steel sheet 10, a plating layer 20 formed on the surface of the base steel sheet 10, and a film 30 formed on the surface of the plating layer 20. The film 30 is, for example, a chemical conversion treatment film.
[0084] In addition, in the present embodiment, when the concentrations (concentration distribution) of C, O, F, Mg, Al, Si, P, Ti, V, Zn, and Zr are continuously measured by line analysis along the thickness direction from the above-mentioned coating toward the surface of the surface-treated steel plate, the position where the concentration of Zn first reaches less than 35.0 mass % is set as the interface 25 between the coating 20 and the film 30.
[0085] Furthermore, a region including the interface 25 and between a range of 10 nm from the interface 25 on the plating layer 20 side and a range of 15 nm from the interface 25 on the film 30 side in the thickness direction is defined as a boundary region A.
[0086] The plating layer 20 and the film 30 may be formed on one surface of the base steel plate 10 or may be formed on both surfaces.
[0087] The line analysis is performed using a FE-TEM (Field Emission-Transmission Electron Microscope) equipped with an energy dispersive X-ray analyzer, for example, under the following conditions.
[0088] A test piece was cut out from a surface treated steel plate with a film formed thereon by a low temperature FIB (Focused Ion Beam) method, and the cross-sectional structure of the cut test piece was observed by a transmission electron microscope (TEM) at a magnification (100,000 to 1,000,000 times) at which the entire film and a portion of the Zn phase of the coating entered the field of view. In order to determine the constituent elements of each layer, TEM-EDS (Energy Dispersive X-ray Spectroscopy) was used to continuously measure the concentrations of C, O, F, Mg, Al, Si, P, Ti, V, Zn, and Zr along the thickness direction from the coating toward the surface of the film, which is also the surface of the surface treated steel plate. The acceleration voltage during observation and EDS analysis was set to 200 kV.
[0089] When the plating layer is observed with FE-TEM, it is clear that it is different from the film, so the position that is clearly different from the film can be judged as the plating layer by observation with FE-TEM. The starting point of the line analysis can be set to, for example, any position of the plating layer observed with FE-TEM. In addition, even if the plating layer cannot be fully identified by observation using FE-TEM, as long as the Zn concentration at the starting point of the line analysis using EDS is, for example, 85 mass% or more and both the Mg concentration and the Al concentration are 1.0 mass% or less, the starting point is indeed the plating layer, so there is no need to perform observation using FE-TEM or line analysis using EDS again.
[0090] The end point of the line analysis may be a position where Bmg, etc. (average concentration of Mg, etc. at the central portion B of the film, etc.) described later can be measured and calculated. For example, the end point of the line analysis may be a position at which the thickness of the film is 30%, 20%, or 10% from the surface of the surface-treated steel plate, or the surface of the film (the surface of the surface-treated steel plate), or the surface of the surface-treated steel plate (the surface of the film).
[0091] Although line analysis can also be performed by EPMA, EPMA cannot perform high-magnification observation compared to TEM, and therefore cannot analyze the concentration distribution of each element in the film of the surface-treated steel sheet of this embodiment with high accuracy. Therefore, in this embodiment, line analysis is performed using FE-TEM with an energy dispersive X-ray analyzer.
[0092] Hereinafter, the base material steel plate, the plating layer, and the film will be described respectively.
[0093] <Base Steel Plate>
[0094] The surface treated steel sheet of the present embodiment can obtain excellent corrosion resistance through plating and coating. Therefore, there is no particular limitation on the base steel sheet. The base steel sheet can be determined according to the applicable product, the required strength, the plate thickness, etc., but for example, hot-rolled mild steel sheets and steel strips described in JIS G 3131: 2018 or JIS G 3113: 2018, or hot-rolled steel sheets and steel strips for automobile structures (sometimes collectively referred to as hot-rolled steel sheets), cold-rolled steel sheets and steel strips described in JIS G 3141: 2021 or JIS G 3135: 2018, or automotive workable cold-rolled high-tensile steel sheets and steel strips (sometimes collectively referred to as cold-rolled steel sheets) can be used.
[0095] <Plating>
[0096] The chemical composition of the plating layer of the surface-treated steel sheet of the present embodiment has a zinc (Zn) concentration (content) of 40 mass % to 100 mass % and a Mg concentration (content) of 0 mass % to less than 4.0 mass %. The plating layer is a zinc plating layer or a zinc alloy plating layer.
[0097] Regarding the chemical composition of the plating layer, there is no limitation on the elements other than Zn and Mg, and for example, the chemical composition may be expressed in mass % as follows:
[0098] Al: 0% or more and less than 25.0%,
[0099] Sn: 0% or more and 20% or less,
[0100] Bi: 0% or more and less than 5.0%,
[0101] In: 0% or more and less than 2.0%,
[0102] Ca: 0% or more and 3.0% or less,
[0103] Y: 0% or more and 0.5% or less,
[0104] La: 0% or more and less than 0.5%,
[0105] Ce: 0% or more and less than 0.5%,
[0106] Si: 0% or more and less than 2.5%,
[0107] Cr: 0% or more and less than 0.25%,
[0108] Ti: 0% or more and less than 0.25%,
[0109] Ni: 0% or more and less than 0.25%,
[0110] Co: 0% or more and less than 0.25%,
[0111] V: 0% or more and less than 0.25%,
[0112] Nb: 0% or more and less than 0.25%,
[0113] Cu: 0% or more and less than 0.25%,
[0114] Mn: 0% or more and less than 0.25%,
[0115] Fe: 0% or more and 5.0% or less,
[0116] Sr: 0% or more and less than 0.5%,
[0117] Sb: 0% or more and less than 0.5%,
[0118] Pb: 0% or more and less than 0.5%,
[0119] B: 0% or more and less than 0.5% and
[0120] The rest: impurities.
[0121] Elements other than Zn also include Mg and Al, all of which are optional elements, and their lower limit is 0%. That is, the chemical composition of the coating can also be only Zn and impurities. As needed, the Mg concentration can also be set to more than 0.1%, more than 0.5% or more than 1.0%, or less than 3.5%, less than 3.0% or less than 2.5%. As needed, the Al concentration can also be set to more than 0.1%, more than 0.2%, more than 1.0% or more than 4.0%, or less than 21.0%, less than 17.0% or less than 12.0%. As needed, the Zn concentration can also be set to more than 50%, more than 60%, more than 70%, more than 80%, or more than 85%, or less than 100%, less than 99%, less than 97% or less than 95%.
[0122] The total concentration of impurities is preferably less than 1.0%.
[0123] The chemical composition of the coating layer can be determined by dissolving the coating layer in a 10% HCl aqueous solution containing an inhibitor for inhibiting corrosion of the substrate (base steel plate) (e.g., IBIT manufactured by Asahi Chemical Industries, Ltd.), and analyzing the composition by ICP emission spectrometry.
[0124] The coating weight is not limited, but in order to improve corrosion resistance, it is preferably 10 g / m2 per side. 2 On the other hand, even if the amount of adhesion on each side exceeds 200g / m 2 The corrosion resistance is also saturated, and it becomes economically disadvantageous. Therefore, the adhesion amount is preferably 200g / m 2 the following.
[0125] Furthermore, the type of plating is not limited, and for example, hot-dip plating or electroplating may be used.
[0126] <Coating>
[0127] The coating exists on the plating layer (the surface opposite to the base steel sheet) in the surface-treated steel sheet of the present embodiment. The coating is sometimes referred to as a chemical conversion coating, a base treatment coating, or a surface treatment coating.
[0128] In the present embodiment, a range of 10 nm on the surface side from the interface between the plating layer and the film in the thickness direction and the center of the surface of the film is set as the central portion B of the film.
[0129] The film is a chemical conversion film formed by applying a chemical conversion solution obtained by further adding phosphoric acid and nitric acid to an aqueous solution containing any one of Ti, Zr, and V, Mg, and F, and drying the solution as described below, and the film contains any one of Ti, Zr, and V, Mg, and F, and may also contain P and Si. From the perspective of electrical conductivity, the film does not contain an organic resin.
[0130] In the film (film of the present embodiment) provided in the surface treated steel sheet of the present embodiment, when the maximum concentration of Ti is set to Dti (unit: mass %), the maximum concentration of Zr in mass % is set to Dzr (unit: mass %), and the maximum concentration of V in mass % is set to Dv (unit: mass %), one or more selected from Dti, Dzr, and Dv is 5.0% or more, and the total of one or more selected from Dti, Dzr, and Dv is 25.0% or less. In this case, the barrier property of the film is improved.
[0131] If the respective values become high, the film becomes brittle and the barrier properties decrease, so the total of Dti, Dzr, and Dv is preferably 20.0% or less.
[0132] That is, the surface-treated steel sheet according to the present embodiment satisfies one or more of the formulas (1) to (3) and satisfies the formula (4).
[0133] Dti≥5.0 (1)
[0134] Dzr≥5.0 (2)
[0135] Dv≥5.0 (3)
[0136] Dti+Dzr+Dv≤25.0 (4)
[0137] The average concentration of C (Bc (unit: mass %)) in the central portion B of the film of the present embodiment is less than 10.0%. That is, the surface-treated steel sheet of the present embodiment satisfies the formula (5).
[0138] Bc<10.0 (5)
[0139] If Bc is 10.0% or more, the barrier property of the film is reduced and the corrosion resistance is deteriorated. As described above, from the perspective of conductivity, the film does not substantially contain organic resin (less than 1% by mass). There is no simple measurement method that can confirm that the organic resin is less than 1% by mass by analyzing the film. However, if the blending amount of the organic resin in the surface treatment liquid increases, the C concentration in the film increases. Therefore, in this embodiment, Bc is set to less than 10.0% as an indicator indicating that the organic resin is less than 1% by mass. In order to obtain excellent corrosion resistance, Bc is more preferably less than 6.0%, less than 4.5%, or less than 3.0%. The lower limit of Bc is not limited, so the lower limit of Bc is 0%. As needed, Bc can also be set to more than 0.5%, more than 1.0%, or more than 1.5%.
[0140] In addition, in the film of the present embodiment, the maximum concentration of Mg in the boundary region A, i.e., Amg (unit: mass %), is 2.5 to 25.0%, the average concentration of Mg in the central portion B of the film, i.e., Bmg (unit: mass %), is 0.5 to 5.0%, and the ratio of Amg to Bmg, i.e., Amg / Bmg, is 2.0 or more. That is, Mg is concentrated near the interface. By concentrating Mg near the interface on the basis of containing a predetermined amount of Mg, the barrier property of the film is improved, and the corrosion resistance is improved.
[0141] If Amg is less than 2.5%, Bmg is less than 0.5%, or Amg / Bmg is less than 2.0, the effect of improving the corrosion resistance cannot be fully obtained.
[0142] However, when the Mg concentration of the plated layer is less than 1.0 mass%, the effect cannot be obtained when Amg is less than 5.0%. This is considered to be because Zn occupies a large volume ratio in the plated structure, so in order to suppress the generation of white rust, a stronger Mg-concentrated layer must be formed than a plated layer containing more Mg (1.0% or more). Therefore, when the Mg concentration of the plated layer is 0% or more and less than 1.0% in terms of mass%, Amg is 5.0 to 25.0%.
[0143] On the other hand, when Amg exceeds 25.0%, the adhesion between the plating layer and the film decreases, and the corrosion resistance decreases. When Bmg exceeds 5.0%, a portion where Mg is concentrated is not formed, and the corrosion resistance decreases.
[0144] That is, the surface-treated steel sheet according to the present embodiment satisfies the following formula (6), formula (7), and formula (10).
[0145] 5.0 / M≤Amg≤25.0 (6)
[0146] 0.5≤Bmg≤5.0 (7)
[0147] Amg / Bmg≥2.0 (10)
[0148] Here, M is a constant of M=1 when the Mg concentration in the chemical composition of the plating layer is 0% or more and less than 1.0% by mass%, and is a constant of M=2 when it is 1.0% or more and less than 4.0%.
[0149] As required, Amg may be set to 20.0% or less, 15.0% or less, 12.0% or less, 10.0% or less, or 8.0% or less. In particular, only when the Mg concentration in the above chemical composition of the plating layer is 1.0 mass % or more and less than 4.0 mass %, the upper limit of Amg may be limited, for example, Amg may be set to 12.0% or less, 10.0% or less, 8.0% or less, or 6.0% or less.
[0150] Furthermore, Bmg may be set to 4.0% or less, 3.0% or less, or 2.0% or less, as required.
[0151] There is no need to specify an upper limit of Amg / Bmg, but Amg / Bmg may be set to 20.0 or less, 15.0 or less, or 10.0 or less. Amg / Bmg may be set to 2.5 or more, 3.5 or more, or 4.5 or more as needed.
[0152] Furthermore, F is also an element that improves the barrier properties of the film, and similarly to Mg, after being contained in a predetermined amount in the film, it is concentrated near the interface.
[0153] Specifically, in the film, the maximum concentration of F in the boundary area A, i.e. Af (unit: mass %), is 7.5~40.0%, the average concentration of F in the central part B of the film, i.e. Bf (unit: mass %), is 0.5~15.0%, and the ratio of the above Af to the above Bf, i.e. Af / Bf, is greater than 2.0.
[0154] When Af is less than 7.5%, Bf is less than 0.5%, or Af / Bf is less than 2.0, the effect of improving the corrosion resistance cannot be fully obtained.
[0155] However, when the Mg concentration of the plating layer is less than 1.0 mass%, the effect cannot be obtained when Af is less than 15.0%. This is considered to be because Zn accounts for a large volume ratio in the plating structure, so in order to suppress the generation of white rust, a stronger F concentration layer must be formed than a plating layer containing more Mg. Therefore, when the Mg concentration of the plating layer is 0% or more and less than 1.0% in terms of mass%, Af is 15.0 to 40.0%.
[0156] On the other hand, when Af exceeds 40.0%, the barrier property is impaired by excessive F, and the corrosion resistance is reduced. When Bf exceeds 15.0%, a portion where F is concentrated is not formed, and excellent corrosion resistance cannot be obtained.
[0157] That is, the surface-treated steel sheet according to the present embodiment satisfies the following formula (8), formula (9), and formula (11).
[0158] 15.0 / M≤Af≤40.0 (8)
[0159] 0.5≤Bf≤15.0 (9)
[0160] Af / Bf≥2.0 (11)
[0161] Among them, for M, when the Mg concentration in the above-mentioned chemical composition of the plating layer is greater than 0% and less than 1.0% in terms of mass%, it is a constant of 1 (i.e., M=1), and when it is greater than 1.0% and less than 4.0%, it is a constant of 2 (i.e., M=2).
[0162] Furthermore, it is preferable to satisfy the following formula (20).
[0163] Af / Bf≥2.5 (20)
[0164] If necessary, Af may be set to 38.0% or less, 35.0% or less, 30.0% or less, 25.0% or less, or 20.0% or less. In particular, only when the Mg concentration in the above chemical composition of the plating layer is 1.0 mass % or more and less than 4.0 mass %, the upper limit of Af may be limited, for example, Af may be set to 25.0% or less, 20.0% or less, 16.0% or less, or 12.0% or less.
[0165] Furthermore, Bf may be set to 12.0% or less, 10.0% or less, or 7.5% or less, as required.
[0166] There is no need to specify an upper limit of Af / Bf, but Af / Bf may be set to 50.0 or less, 30.0 or less, 20.0 or less, or 10.0 or less. Af / Bf may be set to 3.0 or more, 3.5 or more, or 4.5 or more as needed.
[0167] In the film of the present embodiment, the average Si concentration Bsi (unit: mass %) in the central portion B of the film is less than 5.0%.
[0168] That is, the surface-treated steel sheet according to the present embodiment satisfies the following formula (12).
[0169] Bsi<5.0 (12)
[0170] If Bsi is 5.0% or more, a barrier film is not formed, and the corrosion resistance is reduced. From the perspective of improving corrosion resistance, Bsi is more preferably 2.0% or less. Bsi can also be set to 1.5% or less, 1.0% or less, or 0.5% or less as needed.
[0171] The lower limit of Bsi is 0%, but Bsi may be set to 0.1% or more.
[0172] In the surface-treated steel sheet of the present embodiment, it is preferable that the average Zn concentration Bzn (unit: mass %) in the central portion B of the film is 1.0 to 30.0%.
[0173] That is, the surface-treated steel sheet according to the present embodiment preferably satisfies the following formula (19).
[0174] 1.0≤Bzn≤30.0 (19)
[0175] The corrosion resistance is improved by the inclusion of Zn in the film. When Bzn is less than 1.0%, the effect cannot be fully obtained. On the other hand, when Bzn exceeds 30.0%, the corrosion resistance is reduced, so it is not preferred. As needed, Bzn can also be set to 25.0% or less, 21.0% or less, or 18.0% or more, or Bzn can be set to 1.5% or more, 2.0% or more, 3.5% or more, or 5.0% or more.
[0176] In the surface treated steel sheet of the present embodiment, it is preferred that: the maximum concentration of Al in the boundary region A, i.e. Aal (unit: mass %), is 5.0 to 20.0%, the average concentration of Al in the central portion B of the film, i.e. Bal (unit: mass %), is 0.2 to 5.0%, and the ratio of Aal to Bal, i.e. Aal / Bal, is 5.0 or more. Bal is more preferably 0.2 to 1.0%.
[0177] That is, the surface-treated steel sheet according to the present embodiment preferably satisfies the following formulas (14) to (16).
[0178] 5.0≤Aal≤20.0 (14)
[0179] 0.2≤Bal≤5.0 (15)
[0180] Aal / Bal≥5.0 (16)
[0181] In this case, the corrosion resistance (white rust resistance) is improved.
[0182] Considering the Al concentration in the plating layer, Aal may be set to 20.0% or less or 15.0% or less. Aal may be set to 0.5% or more, 1.0% or more, 3.0% or more, 7.0% or more, or 10.0% or more.
[0183] Bal may be set to 3.0% or less, 2.0% or less, or 1.0% or less, or may be set to 0.1% or more, or 0.3% or more.
[0184] There is no need to specify the upper limit of Aal / Bal, but Aal / Bal may be set to 80.0 or less, 60.0 or less, or 30.0 or less. Aal / Bal may be set to 7.0 or more, 10.0 or more, or 15.0 or more as needed.
[0185] Preferably, the maximum concentration of P in the boundary region A, namely Ap (unit: mass %), is 10.0 to 25.0%, and the average concentration of P in the central portion B of the film, namely Bp (unit: mass %), is 0.5 to 8.0%.
[0186] That is, the surface-treated steel sheet according to the present embodiment preferably satisfies the formulas (17) to (18).
[0187] 10.0≤Ap≤25.0 (17)
[0188] 0.5≤Bp≤8.0 (18)
[0189] In this case, corrosion resistance improves.
[0190] The coating weight is preferably 150 to 800 mg / m 2 If the adhesion is less than 150mg / m 2 On the other hand, if the adhesion amount exceeds 800 mg / m 2 , sometimes the film becomes thicker and the corrosion resistance of the processed part decreases.
[0191] Furthermore, the Mg concentration Cmg (unit: mass %) at the position closest to the plating layer in the boundary region A (a position 10 nm from the interface on the plating layer side in the thickness direction) is preferably 0% or more and less than 5.0%.
[0192] That is, the surface-treated steel sheet according to the present embodiment preferably satisfies the following formula (13).
[0193] 0≤Cmg<5.0 (13)
[0194] In this case, cracking of the plating layer caused by processing is reduced, so the corrosion resistance of the processed part is improved.
[0195] <Manufacturing method>
[0196] Next, a preferred method for producing the surface-treated steel sheet according to the present embodiment will be described.
[0197] The surface-treated steel sheet of the present embodiment can obtain the effects as long as it has the above-mentioned characteristics regardless of the manufacturing method, but the following manufacturing method is preferred because it can be stably manufactured.
[0198] That is, the surface-treated steel sheet according to the present embodiment can be produced by a production method including the following steps.
[0199] (I) a plating step of forming a plating layer containing zinc or a zinc alloy on the surface of the steel sheet;
[0200] (II) A film forming step of applying a chemical conversion treatment liquid to a steel sheet having a plated layer and heating and drying the coating to form a coating.
[0201] [Plating process]
[0202] In the plating process, a steel material such as a steel plate is immersed in a plating bath containing Zn or a Zn alloy, or electroplated, thereby forming a plating layer on the surface. There is no particular limitation on the method for forming the plating layer. It can be carried out by a common method in a manner that sufficient plating adhesion can be obtained.
[0203] In addition, there is no limitation on the steel sheet to be used in the plating process and its manufacturing method. As the steel sheet immersed in the plating bath, for example, hot-rolled mild steel sheets and strips described in JIS G 3131: 2018 or JIS G 3113: 2018, or hot-rolled steel sheets and strips for automobile structures, cold-rolled steel sheets and strips described in JIS G 3141: 2021 or JIS G 3135: 2018, and workable cold-rolled high-tensile steel sheets and strips for automobiles can be used.
[0204] The composition of the plating bath may be adjusted according to the chemical composition of the desired plating layer.
[0205] After the steel is removed from the plating bath, the amount of plating applied can be adjusted by wiping as necessary.
[0206] When Cmg is set to be 0% or more and less than 5.0%, it is preferable to set the Mg concentration in the plating layer to be 0% by mass or more and 3.0% by mass or less.
[0207] When Aal / Bal is set to 5.0 or more, the Al concentration in the plating layer is preferably set to 0.1 mass % or more.
[0208] [Film forming step]
[0209] In this step, a chemical conversion treatment liquid is applied to a steel sheet having a plated layer, and the coating (chemical conversion treatment coating) is formed by heating and drying.
[0210] When forming the film of the present embodiment, the chemical conversion treatment liquid is an aqueous solution containing any one of Ti, Zr, and V, Mg, and F, and optionally containing Si, to which phosphoric acid and nitric acid are further added.
[0211] By applying such a treatment liquid, specific elements can be concentrated at the interface between the plating layer and the film.
[0212] Specifically, the concentrations of each element in the chemical conversion treatment solution and the concentrations of phosphoric acid and nitric acid are set as follows. Here, the concentrations of phosphoric acid and nitric acid do not include the concentrations of phosphates, nitrates, etc. By simultaneously including phosphoric acid and nitric acid within the above range, while the dissolution of the coating progresses, specific substances are concentrated at the interface between the chemical conversion treatment film and the coating, thereby greatly improving the effect of improving the adhesion.
[0213] Any one or more of Ti, V, Zr: 5.0 to 20.0 g / L
[0214] Mg: 0.7~7.0g / L
[0215] F: 14.4~46.1g / L
[0216] P: 6.8~32.9g / L
[0217] Si: 0.0~0.4g / L
[0218] Phosphoric acid: 10.0~80.0g / L
[0219] Nitric acid: 5.0~40.0g / L
[0220] When Ap and Bp are set within predetermined ranges, it is preferable to set the P concentration in the chemical conversion treatment liquid to 10.0 g / L or more.
[0221] In addition, when Bzn is set to 1.0-30.0% from the perspective of improving corrosion resistance, when the chemical conversion treatment liquid is applied with a roll coater, it is preferred to control the contact time between the treatment liquid and the plated steel sheet so that the Zn concentration in the treatment liquid is set to 0.5-5.0 g / L on a mass basis. The Zn concentration can be adjusted by immersing the plated steel sheet in the treatment liquid or by adding Zn powder. In order to increase Bzn, Zn powder, Zn compound, etc. may also be added to the chemical conversion treatment liquid. Even when Zn powder, Zn compound, etc. are not added to the chemical conversion treatment liquid, Bzn will not become 0% in most cases because Zn diffuses from the coating.
[0222] Examples of Mg contained in the chemical conversion treatment liquid include magnesium fluoride, magnesium nitrate, magnesium sulfate, magnesium chloride, and magnesium acetate.
[0223] As the F contained in the chemical conversion treatment liquid, as a fluorine compound, compounds such as hydrofluoric acid HF, fluoroboric acid BF4H, fluorosilicic acid H2SiF6, fluorozirconic acid H2ZrF6, and fluorotitanic acid H2TiF6 can be exemplified. The compound can also be a combination of one or more. Among them, hydrofluoric acid is more preferred. When hydrofluoric acid is used, more excellent corrosion resistance and coating properties can be obtained.
[0224] When Zr is contained in the chemical conversion treatment liquid, examples of the Zr compound include ammonium zirconium carbonate, hexafluorozirconic acid, and ammonium zirconium hexafluoro.
[0225] In addition, when V is included, examples of V compounds include vanadium pentoxide V2O5, metavanadic acid HVO3, ammonium metavanadate, sodium metavanadate, vanadium oxytrichloride VOCl3, vanadium trioxide V2O3, vanadium dioxide VO2, vanadium oxysulfate VOSO4, vanadium acetylacetonate VO(OC(=CH2)CH2COCH3))2, vanadium acetylacetonate V(OC(=CH2)CH2COCH3))3, vanadium trichloride VCl3, phosphovanadomolybdic acid, etc. In addition, V compounds obtained by reducing a pentavalent vanadium compound to a tetravalent to divalent vanadium compound with an organic compound having at least one functional group selected from the group consisting of a hydroxyl group, a carbonyl group, a carboxyl group, a primary to tertiary amino group, an amide group, a phosphoric acid group, and a phosphonic acid group may also be used.
[0226] When Ti is contained, examples of the Ti compound include ammonium hexafluorotitanate, fluorotitanic acid, and titanium nitrate.
[0227] The method for applying the chemical conversion treatment liquid is not limited, and for example, the chemical conversion treatment liquid can be applied using a roll coater, a bar coater, a sprayer, or the like.
[0228] After the chemical conversion treatment liquid is applied, it is heated to the maximum heating temperature (maximum target temperature (PMT)) within 5 seconds after the application to dry it. The average temperature increase rate to PMT-10°C during heating is preferably 5 to 50°C / s.
[0229] When Aal / Bal is set to 5.0 or more, it is preferred to set the heating to two-stage heating, and make the heating rate in the second half faster than the heating rate in the first half. Specifically, when the time from the start of heating to the temperature reaching 10°C lower than the maximum heating temperature (PMT) (PMT-10°C) is set to t, it is preferred that the average heating rate V2 in the second half from the start of heating to 0.5t to 1.0t is 1.25 times or more of the average heating rate V1 in the first half from the start of heating to 0.5t, that is, V2 / V1≥1.25. Furthermore, in order to set Aal / Bal to 5.0 or more and set the heating to two stages, the heating rate V1 in the first half is preferably set to 5°C / s or more.
[0230] Furthermore, if the furnace time for heating and drying is long, F tends to concentrate near the interface, so Af / Bf increases. For example, if the furnace time is set to 15 seconds or more, Af / Bf can be set to 2.5 or more.
[0231] Furthermore, when heating, it is preferred to blow the steel plate through a punched metal (a steel plate having a plurality of through holes).
[0232] Example
[0233] A metal plate (plated steel plate) having a plated layer having a plated layer composition shown in Table 1 was prepared. The coating weight of the plated layer was set to 70 g / m 2 Metal plate No. 1 is made by electroplating, No. 2 to 8 are made by hot-dip plating, and No. 4 is made by heat treatment (alloying treatment) after hot-dip plating. In Table 1, for example, 99.6% Zn-0.2% Al means a composition containing 99.6% Zn and 0.2% Al, and the same is true for the others. The rest of the plating composition is impurities.
[0234] As the base material of the plated steel sheet, a cold-rolled steel sheet conforming to JIS G3141:2021 is used.
[0235] Table 1
[0236] Metal plate No. Plating composition (mass %) 1 Zn(99.8%) 2 99.6% Zn-0.2% Al 3 97.8% Zn-0.2% Al-0.8% Mg 4 90.2% Zn-9.0% Fe 5 98.2%Zn-0.2%Al-1.2%Mg 6 90.8% Zn-6.0% Al-3.0% Mg 7 87.8% Zn-11.0% Al-3.0% Mg 8 85.0% Zn-11.0% Al-3.8% Mg
[0237] The plated steel sheets were coated with chemical conversion treatment solutions having the compositions shown in Table 4-1, Table 4-2, and Table 5. The chemical conversion treatment solutions were applied using a roll coater. In No. 48 and No. 118, the chemical conversion treatment solutions contained 1.1 wt% of a polyurethane resin as an organic resin component.
[0238] The element concentrations in the chemical conversion treatment solution are obtained by mixing (NH4)2TiF6, (NH4)2ZrF6, V2O5, MgHPO4·3H2O, H3PO4, NH4F, HNO3, Ca(NO3)2·4H2O, C5H 12 O3Si (vinyltrimethoxysilane) is mixed and adjusted as needed.
[0239] After applying the chemical conversion treatment liquid, hot air was blown to the steel plate through the punching metal (steel plate with multiple through holes) within 5 seconds, and the steel plate was heated to the dry plate temperature (PMT) of Table 4-1, Table 4-2, and Table 5 under the conditions of Table 4-1, Table 4-2, and Table 5, and then cooled to 20° C. by air cooling or water cooling by blowing air through the punching metal. Thus, surface treated steel plates No. 1 to 50 and 101 to 120 were obtained.
[0240] Here, the "temperature rise rate V1" in Table 4-1, Table 4-2, and Table 5 is the average temperature rise rate in the first half of the time until the temperature is reached that is 10°C lower than the maximum heating temperature (PMT) (PMT-10°C), and the so-called "temperature rise rate V2" is the average temperature rise rate in the second half of the time until the temperature is reached that is 10°C lower than the maximum heating temperature (PMT) (PMT-10°C).
[0241] The adhesion amount of the chemical conversion coating was set to 400 mg / m2 except for No. 40 and No. 41. 2 No.40 is set to 150mg / m 2 , No.41 is set to 800mg / m 2 .
[0242]
[0243]
[0244]
[0245]
[0246]
[0247]
[0248] A test piece was cut out from the produced chemical conversion treated steel plate by FIB (Focused Ion Beam) processing with cooling function, and the cross-sectional structure of the cut test piece was observed by a field emission transmission electron microscope (FE-TEM: Field Emission-Transmission Electoron Microscope) with an energy dispersive X-ray analyzer at a magnification at which the entire film and the plating layer entered the observation field.
[0249] At this time, since there are Al phase, MgZn2 phase, and Zn phase in the coating, the Zn phase is confirmed by contrast (the relatively bright part of the dark field image is judged as the Zn phase), and the concentration distribution of C, O, F, Mg, Al, Si, P, Ti, V, Zn, and Zr from the position confirmed as the coating to the surface of the surface-treated steel plate by EDS analysis, where the Zn concentration of the Zn phase is 85% or more and both the Mg concentration and the Al concentration are 1.0% or less, is measured using an energy dispersive X-ray analyzer. The results are shown in Tables 6-1 to 9. In addition, Figure 2 2 shows the depth-direction element distribution measurement results of Test No. 40 of the example.
[0250]
[0251]
[0252]
[0253]
[0254]
[0255]
[0256] Furthermore, the white rust resistance of the plane portion (flat portion) (plane portion corrosion resistance), the corrosion resistance of the processed portion, and the electrical conductivity were evaluated by the following methods. The results are shown in Tables 10-1, 10-2, and 11.
[0257] <Corrosion resistance of flat surface>
[0258] For flat test pieces (70 mm × 150 mm rectangular test pieces), a neutral salt spray test according to JIS Z 2371: 2015 was carried out at a salt concentration of 70 g ± 5 g / L for 72, 120, 168, and 240 hours, and the corrosion resistance was evaluated by the generation of white rust (area ratio) of the test pieces after the test. The evaluation criteria for corrosion resistance are shown below. If it is SSS or SS after 168 hours, it is judged to have sufficient corrosion resistance.
[0259] (Evaluation criteria for corrosion resistance)
[0260] SSS: 3% or less
[0261] SS: more than 3% and less than 5%
[0262] S: more than 5% and less than 10%
[0263] A: More than 10% and less than 30%
[0264] B: More than 30% and less than 50%
[0265] C: More than 50%
[0266] <Corrosion resistance of processed parts (white rust resistance)>
[0267] The center of the flat test piece (70 mm × 150 mm rectangular test piece) was subjected to the Erichsen test (extruded 7 mm), and then subjected to the salt spray test according to JIS Z 2371: 2015 for 72 hours to observe the occurrence of white rust in the extruded part. The evaluation criteria were the same as those for the flat part corrosion resistance, and if it was SS or S, it was judged to have sufficient corrosion resistance.
[0268] (Evaluation criteria for corrosion resistance)
[0269] SS: more than 5% and less than 10%
[0270] S: more than 10% and less than 30%
[0271] A: More than 30% and less than 50%
[0272] B: More than 50%
[0273] <Conductivity>
[0274] Using JIS C 2550-4:2011 A method, the total area of 10 contact electrodes is 1000mm 2 The interlayer resistivity is determined under the conditions of
[0275] If it is A, it is judged that the conductivity is sufficient.
[0276] (Evaluation criteria for electrical conductivity)
[0277] A: Interlayer resistivity is less than 300Ω·mm 2
[0278] C: interlayer resistivity is 300Ω·mm 2 above
[0279] Table 10-1
[0280]
[0281] Table 10-2
[0282]
[0283] Table 11
[0284]
[0285] As can be seen from Tables 1 to 11, Test Nos. 1 to 23, 40 to 42, 50, 101 to 106, and 120, which have a steel sheet, a plating layer, and a film, and have an element distribution specified in the present invention in the range from the plating layer to the surface of the film, are excellent in both corrosion resistance and conductivity.
[0286] On the other hand, Test Nos. 24 to 39, 43 to 49, and 107 to 119, whose element distributions were outside the scope of the present invention, were inferior in corrosion resistance. Furthermore, Nos. 48 and 118, which contained organic resins, were also inferior in electrical conductivity.
[0287] Industrial Applicability
[0288] According to the present invention, a surface-treated steel sheet having excellent corrosion resistance and electrical conductivity can be provided, and the present invention has high industrial applicability.
[0289] Explanation of symbols
[0290] 1 Surface treated steel plate
[0291] 10. Base material steel plate (steel plate)
[0292] 20 coating (zinc coating or alloyed zinc coating)
[0293] 30 Film (chemical conversion treatment film)
[0294] 25 Interface
[0295] A Boundary area
[0296] B Central part of the membrane
Claims
1. A surface treated steel plate, characterized in that: It has: Base steel plate, a plating layer formed on the surface of the base steel plate, and a film formed on the surface of the plated layer, The Zn concentration of the plating layer is 40 mass % or more and 100 mass % or less, and the Mg concentration is 0 mass % or more and less than 4.0 mass %, When the concentrations of C, O, F, Mg, Al, Si, P, Ti, V, Zn, and Zr are continuously measured by line analysis along the thickness direction from the coating layer toward the surface of the surface-treated steel sheet, The position where the Zn concentration first reaches 35.0 mass % or less is set to be the interface between the plating layer and the film, The boundary region is defined as a region between a range of 10 nm from the interface on the plating layer side and a range of 15 nm from the interface on the film side in the thickness direction. The range of 10 nm from the center of the interface and the surface of the film in the thickness direction on the surface side is defined as the center of the film. In this case, the surface treated steel sheet satisfies at least one of the following formulas (1) to (3) and (4) to (12), Dti≥5.0 (1) Dzr≥5.0 (2) Dv≥5.0 (3) Dti+Dzr+Dv≤25.0 (4) Bc<10.0 (5) 5.0 / M≤Amg≤25.0 (6) 0.5≤Bmg≤5.0 (7) 15.0 / M≤Af≤40.0 (8) 0.5≤Bf≤15.0 (9) Amg / Bmg≥2.0 (10) Af / Bf≥2.0 (11) Bsi<5.0 (12) wherein Dti is the maximum concentration of Ti in mass % between the interface and the center of the thickness direction from the interface to the surface, The Dzr is the maximum concentration of Zr in mass % between the interface and the center of the thickness direction from the interface to the surface, The Dv is the maximum concentration of V in mass % between the interface and the center of the thickness direction from the interface to the surface, The Bc is the average concentration of C in the central portion of the film in mass %, Amg is the maximum concentration of Mg in the boundary region of the film in terms of mass %, Bmg is the average concentration of Mg in the central portion of the film in terms of mass %, Af is the maximum concentration of F in the boundary region of the film in terms of mass %, The Bf is the average concentration of F in the central portion of the film in mass %, The Bsi is the average concentration of Si in the central portion of the film in mass %, When the Mg concentration of the plating layer is 0 mass % or more and less than 1.0 mass %, M is a constant of 1, and when the Mg concentration of the plating layer is 1.0 mass % or more and less than 4.0 mass %, M is a constant of 2.
2. The surface-treated steel sheet according to claim 1, characterized in that: Further satisfying the following formula (13), 0≤Cmg<5.0 (13) Here, Cmg is the concentration of Mg in mass % at a position 10 nm from the interface on the plating layer side in the thickness direction of the plating layer.
3. The surface treated steel sheet according to claim 1 or 2, characterized in that: Further satisfying the following equations (14) to (16), 5.0≤Aal≤20.0 (14) 0.2≤Bal≤5.0 (15) Aal / Bal≥5.0 (16) Here, Aal is the maximum concentration of Al in the boundary region expressed in mass %, and Bal is the average concentration of Al in the central portion of the film expressed in mass %.
4. The surface-treated steel sheet according to any one of claims 1 to 3, characterized in that: Further satisfying the following equations (17) to (18), 10.0≤Ap≤25.0 (17) 0.5≤Bp≤8.0 (18) Here, Ap is the maximum concentration of P in the boundary region expressed in mass %, and Bp is the average concentration of P in the central portion of the film expressed in mass %.
5. The surface-treated steel sheet according to any one of claims 1 to 4, characterized in that: Further satisfying the following formula (19), 1.0≤Bzn≤30.0 (19) Here, the Bzn is an average concentration of Zn in the central portion of the film in terms of mass %.
6. The surface-treated steel sheet according to any one of claims 1 to 5, characterized in that: Further satisfying the following formula (20), Af / Bf ≥ 2.5 (20).
Citation Information
Patent Citations
Chemical conversion coated steel sheet superior in corrosion resistance
JP2002194558A
Zn-Al ALLOY PLATED STEEL SHEET HAVING IMPROVED CORROSION RESISTANCE
JP2003306777A
Hot-dip zinc alloy plated steel sheet having excellent corrosion resistance
JP2007023309A
Chromate-free precoated metal sheet and substrate treatment agent for precoated metal sheet
JP2012237065A